MEWUJUDKAN VISI PENDIDIKAN PROVINSI JAWA TIMUR - Vincentius Luluk Prijambodo (Magister Scientiae, 2016)
As stated in the Constitution of the Republic of Indonesia 1945, the ideal of national education is to educate the life of the nation. Then, in Law Number 20 Year 2003 regarding National Education System, it is mentioned that the Government and Local Government have the right to direct, guide, assist and supervise the implementation of education in accordance with applicable laws and regulations. To implement the mandate of this constitution, East Java Provincial Government prepares Regional Mid-Term Development Plan of East Java Year 2014-2019, where it stipulates that the vision of education and culture of (Education Office) East Java Province is "The realization of smart, creative, and majestic human beings with synergicand global competitiveness.” This article describes some solutive ideas to actualize East Java Province’ seducation vision.